Change in the intestinal bacterial community structure associated with environmental microorganisms during the growth of Eriocheir sinensis. Issue 5 (11th October 2018) - Wang, Chenhe; Zhou, Yanfeng; Lv, Dawei; Ge, You; Li, Huan; You, Yang
Abstract: As an important organ to maintain the host's homeostasis, intestinal microbes play an important role in development of the organism. In contrast to those of terrestrial animals, the intestinal microbes of aquatic organisms are affected by environmental microorganisms (including water microorganisms and sediment microorganisms). In the present study, the compositional differences of intestinal microbes in three representative developmental stages of the Chinese mitten crab ( Eriocheir sinensis ) were studied. Meanwhile, network association analysis, and visualization of the water microorganisms of the crabs' habitat, the environment microorganisms in the pond, and the intestinal microbes, was carried out. The results showed that the gut microbiota diversity index decreased continuously with age, and the four bacteria of Aeromonas (Proteobacteria), Defluviitaleaceae (Firmicutes), Candidatus Bacilloplasma (Tenericutes), and Dysgonomonas (Bacteroidetes) were the "indigenous" flora of the crab. In the network‐related analysis with the environment, we found that as the culture time increased, the effect of environmental microorganisms on the intestinal microbes of crabs gradually decreased, and the four "indigenous" bacteria were always unaffected by the environmental microorganisms. The results of this study identified the core bacteria of the crab and, for the first time, studied the relationship between intestinal environmental microorganisms, which will aid the practical production of crabs and will promote research into the relationship between specific bacteria and the physiological metabolism of crabs. Abstract : In this study, the compositional differences of intestine microbes in three representative stages of the culture stage of the Chinese mitten crab ( Eriocheir sinensis ) were selected, meanwhile the network association analysis and visualization of the water microorganisms of the crab original living area, the environment microorganisms of the pond and the intestine microbes were carried out.